Teaching Materials for Thematic Learning Courses to Improve Elementary School Prospective Teachers’ Critical Thinking Skills - Ana, Ria Fajrin Rizqy; Asriyanti, Frita Devi; Syafiah, Rohmatus (LPPM Undiksha, 2023)
Thematic learning emphasizes the application of the concept of learning by doing in the classroom and the application of the concept of learning by playing. The problems that occur are that the implementation of learning is still fixated on separate subjects that are not in accordance with the learning themes used, the learning process is teacher-centered, the unavailability of learning tools in accordance with thematic characteristics. This study aims to develop thematic learning teaching materials for PGSD study program students and test the effectiveness of their products. The model used is a research and development (R&D) model with a Dick & Carey design model. The research instruments used were questionnaires, tests, interviews, and documentation. The results of the research are in the form of teaching material products. The results of the validation of these teaching materials obtained scores from learning experts of 75%, material experts of 81.66%, and media experts of 76%. The teaching materials developed are very effective and feasible to use based on the results of the paired sample t test with the results of P < 0.000, df = 29, t = -51.470.